Nouns and verbs in the brain: Implications of linguistic typology for cognitive neuroscience - Kemmerer, David; Eggleston, Alyson (Lingua, 2010)
Abstract: In recent years, cognitive neuroscience has generated many important findings about how the noun–verb distinction is implemented in the brain, but at the same time it has largely ignored equally important advances in linguistic typology concerning the nature of grammatical categories. Following the lead of Evans and Levinson (2009), we argue that typological data and theory have significant implications not only for the interpretation of recent neuroscientific discoveries about the noun–verb distinction, but also for the direction of future neuroscientific research on this topic.